2021
DOI: 10.1007/s11192-020-03814-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring WorldCat identities as an altmetric information source: a library catalog analysis experiment in the field of Scientometrics

Abstract: Assessing the impact of scholarly books is a difficult research evaluation problem. Library Catalog Analysis facilitates the quantitative study, at different levels, of the impact and diffusion of academic books based on data about their availability in libraries. The WorldCat global catalog collates data on library holdings, offering a range of tools including the novel WorldCat Identities. This is based on author profiles and provides indicators relating to the availability of their books in library catalogs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One of the challenges in collecting altmetrics for the social sciences is that citation analysis databases primarily indexed journal articles (Torres-Salinas et al, 2021), but are limited in their coverage of books, which are commonly used by social science scholars (Nederhof, 2006) and are known have educational and public interest value . Tracking the circulation of books on social media is challenging because altmetric tools often rely on the use of Digital Object Identifiers (DOIs), but proceedings, edited volumes, and monographs in the Social Sciences and Arts & Humanities do not typically assign them (Gorraiz et al, 2016).…”
Section: Altmetrics In the Social Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges in collecting altmetrics for the social sciences is that citation analysis databases primarily indexed journal articles (Torres-Salinas et al, 2021), but are limited in their coverage of books, which are commonly used by social science scholars (Nederhof, 2006) and are known have educational and public interest value . Tracking the circulation of books on social media is challenging because altmetric tools often rely on the use of Digital Object Identifiers (DOIs), but proceedings, edited volumes, and monographs in the Social Sciences and Arts & Humanities do not typically assign them (Gorraiz et al, 2016).…”
Section: Altmetrics In the Social Sciencesmentioning
confidence: 99%
“…Furthermore, Kousha and Thelwall (2014) studied the citation impact of academic books in Science, Social Sciences, and the Humanities and found that Google Books citations outnumber the Web of Science Book Citation Index. Erfanmanesh et al (2019) successfully used Bookmetrix to investigate the disciplinary differences in citations, downloads, social media mentions, and reference manager readerships of books in four disciplines published by a single publisher, while Torres-Salinas et al (2021) showed that WorldCat Identities can be a useful tool for book impact assessment, but noted that the value of its data is undermined by the vast collections of ebooks held by academic libraries.While these databases show promise for exploring the impact of books broadly, Yang et al (2021) explored the impact of academic books in the Book Citation Index from Web of Science published between in 2013-2017 and found that the coverage of DOIs and, as a result, of altmetric values, remains low.…”
Section: Altmetrics In the Social Sciencesmentioning
confidence: 99%
“…White et al (2009) explicitly draw the analogy between libcitations and citation analyses, inviting readers to think about library union catalogues as "librarian's citation indexes," reflecting the cumulative judgments of librarians. Studies exploring the correlation between citation and libcitation indicators have found "positive but weak" correlations between libcitations and citations (Torres-Salinas et al, 2021;Zuccala & White, 2015) and strong links between citation rates and library holding rates for English books, but not for Dutch books (Linmans, 2010). According to Zuccala and Guns (2013), "citations and libcitations are not entirely interchangeable."…”
Section: Introductionmentioning
confidence: 99%
“…A discussion about the problem of massive collections of ebooks has emerged recently in an analysis of WorldCat Identities (WI) for author level indicator of book holdings, where 398 most prolific book authors in information science were identified with false assignment of book titles and thus an inordinate number of holding counts that originated from ebooks (Torres-Salinas, Arroyo-Machado and Thelwall, 2020). A previous investigation into print and electronic holdings also showed that the average number of electronic holdings for each title is about 7 times more numerous than print holdings (Maleki, 2021), showing that a significant part of electronic holding is included in total library holding counts.…”
Section: Introductionmentioning
confidence: 99%